AMDAL-BASED RISK IDENTIFICATION IN THE EAST SURABAYA HOSPITAL CONSTRUCTION PROJECT - Djatmiko, Mochammad; Patriadi, Andi; Sajiyo, Sajiyo (International Journal of Social Service and Research, 2025)
The East Surabaya Hospital construction project is one of the most important projects in the healthcare sector. The objective of this study was to identify, analyze, and proactively manage risks that could potentially affect the success of the hospital construction project. This research uses a descriptive-analytical approach with mixed methods to identify and analyze the dominant risks affecting the project success. The results of this research show that comprehensive risk management is a crucial element to ensure project success, with the implementation of measures such as routine maintenance of heavy equipment, efficient procurement of materials, proactive communication with communities and accelerated coordination between agencies for licensing. Furthermore, the results of regression analysis also show that this approach contributed significantly to the achievement of project objectives, with indicators of success including on-time completion, costs within budget, and quality of results that met standards. Therefore, this research serves as a model that can be applied to similar projects, especially those with significant impacts on the environment and surrounding communities.